Treatment and relapse of interstitial lung disease in nivolumab‐treated patients with non–small cell lung cancer. Issue 4 (24th February 2021) - Sata, Masafumi; Sasaki, Shinichi; Oikado, Katsunori; Saito, Yoshinobu; Tominaga, Junya; Sakai, Fumikazu; Kato, Terufumi; Iwasawa, Tae; Kenmotsu, Hirotsugu; Kusumoto, Masahiko; Baba, Tomohisa; Endo, Masahiro; et al.
Abstract: Nivolumab, a human monoclonal antibody against programmed death‐1, is approved for the treatment of non–small cell lung cancer (NSCLC). Although nivolumab is generally well tolerated, it can cause interstitial lung disease (ILD), a rare but potentially fatal immune‐related adverse event. Currently, there are limited data available on the treatment of nivolumab‐induced ILD and its outcome. This retrospective cohort study based on a post–marketing study described the treatment of nivolumab‐induced ILD and its outcome in NSCLC patients in Japan through the assessment of clinical and chest imaging findings by an expert central review committee. Treatment details for patients who experienced a relapse of ILD were also analyzed. Of the 238 patients identified as having nivolumab‐induced ILD, 37 patients died of ILD. Corticosteroids were used in 207 (87.0%) patients. Of those, 172 (83.1%) patients responded well and survived and 35 (16.9%) died (most died during corticosteroid treatment). A total of nine patients experienced a relapse; at the time of relapse, four patients were taking nivolumab. Of those who were receiving corticosteroids at the time of relapse, three of four patients were taking low doses or had nearly completed dose tapering. All patients (except one, whose treatment was unknown) received corticosteroids for the treatment of relapse, but one patient died. Patients with NSCLC who experience nivolumab‐induced ILD are treated effectively with corticosteroids, and providing extra care when ceasing or reducing the corticosteroid dose may prevent relapse of ILD. Abstract : Use of nivolumab in the treatment of non–small cell lung cancer may be associated with interstitial lung disease. Our post–marketing study suggests that nivolumab‐induced interstitial lung disease can be treated effectively with corticosteroids. To prevent a relapse, extra care should be provided when ceasing or reducing the corticosteroid doses.